Fiscal cycles and the Brazilian states: an analysis of the mechanisms behind term limits - Cabral, André Dantas (2017)
The objective of this thesis is to observe if a political business cycle is in effect on the Brazilian states. It also aims to observe how the institution of term limits, aligned with a resign-to-run law, is affecting the fiscal behavior of the states. It does so by testing two possible mechanisms trough, which term limits may be acting: reelections and resignations. The results suggest that there is a political fiscal cycle happening on the state level, with an increase in expenditures before elections followed by a steep decline afterwards. Term limitation also perform an important role in this cycle, with states experiencing lower expenditures when an incumbent faces a limit. A more detailed analysis of the phenomenon showed that this difference was not the result of an increase in expenditures for non-limited incumbents driven by the possibility of reelection, but by a decrease in expenditures for limited incumbents driven by an increase in resignations. This study strengthen the literature on sub-national political cycles by showing that those cycles are still present at the Brazillian state level. It also explores an alternative and yet understudied mechanism through which term limits affects fiscal behavior (in conjoint with a resign-to-run law), resignations. In doing so, this study highlights the importance of mechanism analysis when observing the fiscal effects of different institutions.